Reactive jet impingement bioprinting of high cell density gels for bone microtissue fabrication. (27th December 2018) - da Conceicao Ribeiro, Ricardo; Pal, Deepali; Ferreira, Ana Marina; Gentile, Piergiorgio; Benning, Matthew; Dalgarno, Kenneth
Abstract: Advances in three-dimensional cell cultures offer new opportunities in biomedical research and drug development. However, there are still challenges to overcome, including the lack of reliability, repeatability and complexity of tissues obtained by these techniques. In this study, we describe a new bioprinting system called reactive jet impingement (ReJI) for the bioprinting of cell-laden hydrogels. Droplets of gel precursor solutions are jetted at one another such that they meet and react in mid-air before the gel droplets fall to the substrate. This technique offers a combination of deposition rate, cell density and cell viability which is not currently matched by any other bioprinting technique. The importance of cell density is demonstrated in the development of bone microtissues derived from immortalised human bone marrow stem cells. The cells were printed with high viability within a collagen-alginate-fibrin gel, and tissue specific gene expression shows significantly higher tissue maturation rates using the ability of the ReJI system to deposit gels with a high cell density.